Evidence of the Disassembly of ?-Cyclodextrin-Octylamine Inclusion Compounds Conjugated to Gold Nanoparticles Via Thermal and Photothermal Effects - Silva-Gonzalez, N; Silva-Gonzalez, N (Multidisciplinary Digital Publishing Institute (MDPI), 2016)
Cyclodextrin (CD) molecules form inclusion compounds (ICs), generating dimers that are capable of encapsulating molecules derived from long-chain hydrocarbons. The aim of this study is to evaluate the structural changes experienced by ICs in solution with increasing temperatures. For this, a nuclear magnetic resonance (1H-NMR) titration was performed to determinate the stoichiometric α-cyclodextrin (α-CD):octylamine (OA) 2:1 and binding constant (k = 2.16 M-2) of ICs. Solution samples of αCD-OA ICs conjugated with gold nanoparticles (AuNPs) were prepared, and 1H-NMR spectra at different temperatures were recorded. Comparatively, 1H-NMR spectra of the sample irradiated with a laser with tunable wavelengths, with plasmons of conjugated AuNPs, were recorded. In this work, we present evidence of the disassembly of ICs conjugated with AuNPs. Thermal studies demonstrated that, at 114 °C, there are reversible rearrangements of the host and guests in the ICs in a solid state. Migration movements of the guest molecules from the CD cavity were monitored via temperature-dependent 1H-NMR, and were verified comparing the chemical shifts of octylamine dissolved in deuterated dimethylsulfoxide (DMSO-d6) with the OA molecule included in α-CD dissolved in the same solvent. It was observed that, at 117 °C, OA exited the α-CD cavity. CD IC dimer disassembly was also observed when the sample was irradiated with green laser light. © 2016 by the authors; licensee MDPI, Basel, Switzerland.